A reusable learning object for assessment cardiovascular and respiratory responses - Rueda Díaz, Leidy Johanna; Mercado Miranda, David Alejandro; Padilla García, Clara Inés (Investigación y Educación en Enfermería, 2023)
Objective. Produce and determine the validity of a reusable learning object for assessment cardiovascular and respiratory responses from the taxonomy of the North American Association of Nursing Diagnosis Domain 4. Activity/Rest, Class 4. Cardiovascular/Pulmonary Responses. Methods. A descriptive methodological study was developed that included three phases (1) construction of the reusable learning object incorporating Gagné's nine instructional events, (2) content validation was carried out with 24 nurses who served as experts, and (3) and Usability was evaluated by 22 nursing students from a Public University in Colombia. Results. The reusable learning object was organized into three modules: introduction, assessment of cardiovascular responses, and assessment of pulmonary responses. The learning object obtained a content validation index of 0.86; the usability indicators had proportions of agreement greater than 85%. Conclusion. The reusable learning object is valid and can be used for teaching the assessment of cardiovascular and respiratory responses in nursing students.